Mapping Ecotourism Policy Studies in Indonesia: The 3C Approach - Conservation, Community, and Control - Yusuf, Muhamad; Kurniasih, Denok (Journal of Local Government Issues, 2023)
This study seeks to investigate the evolution of studies on ecotourism policy in Indonesia. Using the Scopus and Google Scholar databases, a systematic literature review was conducted to identify articles relating to ecotourism policies in Indonesia. This study's results mapped out the discussions that had taken place and identified the three main subtopics that researchers had discussed. First, "Focusing on Conservation" discusses the significance of protecting nature and minimizing the environmental impact of tourism. Second, "Strengthening the Communities" emphasizes that engaging local communities in decision-making and empowering them economically can increase tourism participation. Third, "Ensuring Regulatory Control" discusses law enforcement, policymaking, and government oversight of sustainable tourism. This study discusses the type of main issue of ecotourism policy studies in Indonesia. This discussion map emphasizes the significance of striking a balance between nature conservation, local community empowerment, and regulation control in ecotourism development. The identification of research gap and future research direction also proposed here. Thus, this study's findings can serve as the basis for future research and contribute to the formulation of more effective policies for promoting sustainable ecotourism in Indonesia.